Arabidopsis Glutamate Receptor Homolog3.5 Modulates Cytosolic Ca2+ Level to Counteract Effect of Abscisic Acid in Seed Germination . Issue 4 (13th February 2015) - Kong, Dongdong; Ju, Chuanli; Parihar, Aisha; Kim, So; Cho, Daeshik; Kwak, June M.
Abstract : A Ca 2+ signal mediated by a glutamate receptor homolog promotes seed germination, opposing the effect of abscisic acid. Abstract: Seed germination is a critical step in a plant's life cycle that allows successful propagation and is therefore strictly controlled by endogenous and environmental signals. However, the molecular mechanisms underlying germination control remain elusive. Here, we report that the Arabidopsis ( Arabidopsis thaliana ) glutamate receptor homolog3.5 ( AtGLR3.5 ) is predominantly expressed in germinating seeds and increases cytosolic Ca 2+ concentration that counteracts the effect of abscisic acid (ABA ) to promote germination. Repression of AtGLR3.5 impairs cytosolic Ca 2+ concentration elevation, significantly delays germination, and enhances ABA sensitivity in seeds, whereas overexpression of AtGLR3.5 results in earlier germination and reduced seed sensitivity to ABA . Furthermore, we show that Ca 2+ suppresses the expression of ABSCISIC ACID INSENSITIVE4 ( ABI4 ), a key transcription factor involved in ABA response in seeds, and that ABI4 plays a fundamental role in modulation of Ca 2+ -dependent germination. Taken together, our results provide molecular genetic evidence that AtGLR3.5-mediated Ca 2+ influx stimulates seed germination by antagonizing the inhibitory effects of ABA through suppression of ABI4. These findings establish, to our knowledge, a new and pivotal role of the plant glutamate receptor homolog and Ca 2+ signaling in germination control and uncover the orchestrated modulation of the AtGLR3.5-mediated Ca 2+ signal and ABA signaling via ABI4 to fine-tune the crucial developmental process, germination, in Arabidopsis.